2014
DOI: 10.1007/s10815-014-0233-0
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene expression patterns in rabbit preimplantation embryos developed in vivo and in vitro

Abstract: Purpose The levels and timing of expression of genes like BCLXL, HDAC1 and pluripotency marker genes namely, OCT4, SOX2, NANOG and KLF4 are known to influence preimplantation embryo development. Despite this information, precise understanding of their influence during preimplantation embryo development is lacking. The present study attempts to compare the expression of these genes in the in vivo and in vitro developed preimplantation embryos. Methods The in vivo and in vitro developed rabbit embryos collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…Particularly, the expression of POU5F1 could be followed in developing embryos of POU5F1 promoter-EGFP transgenic rabbits (Yin et al, 2013). In another study, the expression level of POU5F1, SOX2, NANOG and KLF4 was measured by quantitative PCR during rabbit preimplantation development (Henderson et al, 2014). In agreement with our results, it was shown that these genes are expressed during this period, and were suggested to be key regulators of rabbit preimplantation development.…”
Section: Expression Of the Rabbit Pluripotency-associated Genes Durinsupporting
confidence: 85%
“…Particularly, the expression of POU5F1 could be followed in developing embryos of POU5F1 promoter-EGFP transgenic rabbits (Yin et al, 2013). In another study, the expression level of POU5F1, SOX2, NANOG and KLF4 was measured by quantitative PCR during rabbit preimplantation development (Henderson et al, 2014). In agreement with our results, it was shown that these genes are expressed during this period, and were suggested to be key regulators of rabbit preimplantation development.…”
Section: Expression Of the Rabbit Pluripotency-associated Genes Durinsupporting
confidence: 85%
“…During the preimplantation stage of embryos, paternal and maternal genomes undergo dramatic reprogramming changes, particularly embryonic genome activation (EGA) . EGA of rabbit embryos generally occurs at the 8‐cell stage and is characterized by strict temporal and stage‐specific gene regulation . In particular, DNA methylation, an important epigenetic modification, plays a crucial role in regulating gene expression and other biological processes .…”
Section: Discussionmentioning
confidence: 99%
“…36 EGA of rabbit embryos generally occurs at the 8-cell stage and is characterized by strict temporal and stage-specific gene regulation. 32,37 In particular, DNA methylation, an important epigenetic modification, plays a crucial role in regulating gene expression and other biological processes. 38 DNA methylation states are altered by in vitro culture conditions of preimplantation stage rabbit embryos.…”
Section: Discussionmentioning
confidence: 99%
“…One of the highly connected downregulated genes was NANOG, well-known as a pluripotency-sustaining factor in embryonic stem cells [63]. In rabbits, lower NANOG expression has been found in in vivo embryos at the 16 cell, morula, and blastocyst stages compared to the same stages in in vitro produced embryos [64]. Since NANOG expression is restricted to the embryoblast (EB) and is repressed in trophectoderm (TE) cells [65], this lower expression in the total blastocyst could derive from a different ratio of the number of EB and TE cells at a given stage in in-vitro-produced and in vivo embryos.…”
Section: Unveiling the Potential Of Oev Rna Components To Regulate Emmentioning
confidence: 99%